Effects of preemptive ketamine on postoperative analgesia after total abdominal hysterectomy (TAH) under general anaesthesia - Ahmed, Giash Uddin; Mondal, Montosh Kumar; Roy, Beauty Rani; Badrudozza, ANM; Yeasmeen, Sabina; Bhowmick, Dilip Kumar; Akhtaruzzaman, AKM (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background The concept of ‘Pre-emptive analgesia’ suggest that the best post operative pain management begins preoperatively. Preemptive low dose ketamine is effective in treating post operative pain after total abdominal hysterectomy. Objectives This study was designed to evaluate the analgesic efficacy of preemptive low dose ketamine in treating moderate to severe acute post operative pain in total abdominal hysterectomy surgery under general anesthesia. Methods Sixty patients aged between 35-50 years, weight between 45-65 kg with ASA physical status I & II underwent elective total abdominal hysterectomy under general anesthesia were randomly divided into two groups. In group A, patients received 10 ml of normal saline I/V over 60-90 second before surgical incision. In group B, patients received 0.15 mg/kg ketamine (mixed with 10 ml normal saline) I/ V over 60-90 second before surgical incision. Anesthetic technique was standardized & patients were interviewed regularly. Pain score, analgesic consumption, side effects & quality of recovery score were recorded for 24 hours. Results Patient received preemptive ketamine had a statistically significant lower pain score in first 24 hours after operation compared with placebo group. Mean value of first analgesic demand in group A was 25.67±1.60 & group B was 57.33±2.97 & p = 0.00. Mean value of total opioids consumption in group A was 290.00±9.09 & group B was 210.67±7.01 & p = 0.00. Significant differences were observed between two groups regarding first analgesic demand & total analgesic consumption. There were no significant differences between these two groups in respect to haemodynamic variable or side effects. Conclusion Preemptive low dose intra venous ketamine offer a safe, non opioid, well-tolerated analgesia with efficacy in moderate to severe post operative pain & spare opioid consumption in the post operative pain management. JBSA 2012; 25(1): 3-8